Só a água sustenta o nosso peso - Miranda, Camila Fontenele de (2022)
Although the efforts of researchers in the fat studies in the west, especially nowadays, these studies are often reduced to findings only on health and beauty, hiding a colonial and imperial heritage. It is concealed that the hatred on fatness in the west, later in the Americas, is related to the readings that Europeans had about non-western peoples, especially Africans. Though the belly of the European bourgeois coexists in this historicizing, where a “positive image” of fatness was merely projected and a certain privilege for those who had it, even though there were many reservations, adiposity quickly came to be understood as a flaw (something morally wrong) until its effective pathologization. Therefore, the development of anti-fatness politics that go hand in hand with anti-blackness politics. That's because the colonial imagination, heritage from the era of navigation abroad conducted by travelers, ethnographers, doctors, artists, and anthropologists, was (and still is) updated, distorting the perspective of a body that exists beyond dichotomies. It is ignored that grease is an ambiguous and complex substance since the power fictions in the civilizing project of the body conjugates it in a single tense: the past. In other words, the existence of fatness needs to be exterminated due to an ideal of a human being of a certain color situated in a measured up to nation. Hence, this multispecies/interspecies research permeates the questioning and tensioning of the power fictions in which we are inserted. Consequently, if the fat body is a life to be annihilated, how can we reimagine our presence? If grease is ambiguous in understanding and form, would we be able to shape futures through it? Would it be possible to radically imagine the fat body through whales? Although resorting to the theoretical-methodological framework proposed by the feminist theorists Donna Haraway, in Speculative Fabulation, and Gloria Anzaldúa, in Nepantla, to conjecture possibilities in the face of these questions, the procedures that cross this research are outlines of slippery practices, informed by the blue and black writings that intersect the intimacy of marine mammals and fat people. Thus, given the impossibility of synthesis, this investigation shows that scrutinizing the body is never a linear process, much less an individual one. Finally, when stating that only water sustains our ponderosity, it is suggested that this “support” is understood beyond the gesture of displacing the fat body in the water, above all, it connects with the return of being mammalian, wild, and aquatic, even inhabiting the terrestrial environment for a longer time.